An Indoor/Outdoor Detection Method based on Smartphone - Nguyễn, Hữu Khánh (2023)
In this paper, an effective method is suggested to detect whether a user is indoor or outdoor environment based on a set of sensors in a smartphone. There are not many tools or applications to detect the indoor/outdoor environment accurately but the environment information is useful for many location-based and context-aware applications such as indoor localization or activity recognition. The proposed methods attempts to classify current environment using a combination of six different types of sensors (Wifi module, the magnetometer, the status of battery charging, the GPS, the microphone, and the light sensor). The performance of the proposed methods is verified experimentally.